Effect of Carbamazepine on the Serum Level of Thyrotropin-Releasing Hormone - Kalsoom, Ume; Ali, Niaz (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The thyroid gland is endocrine gland located in front and lower side of neck. Thyroid gland secretes two types of thyroid hormones that are triiodothyronine (T3) and tetraiodothyronine (T4). The hypothalamus is a center for regulation of thyroid hormones. It senses the low hormone levels and in turn releases thyrotropin-releasing hormone (TRH). TRH stimulates anterior pituitary to release TSH which then acts on the thyroid gland to maintain normal level of T3 and T4. The objective of study is to determine the effects of carbamazepine on TRH in euthyroid rabbits. Methods: An experimental study performed on 30 rabbits. These were divided into three groups having 10 rabbits in each group. 10 rabbits were treated with 10mg/kg/day of CBZ (OD), other 10 with 35mg/kg/day CBZ (three divided doses) and 10 rabbits served as control. T3, FT4, TSH and TRH levels were evaluated at baseline and after 21 days of treatment in all three groups by Electro-chemiluminescence immunoassay and ELISA respectively. Results: Comparison of the hormone levels of the control group and the group having a dose of 10 mg/kg/day for 21 day of treatment. Comparative results showed serum level of T3 (P=0.031), FT4 (P=0.030), and TRH (P=0.044) levels significantly lower than the control group and TSH (P=0.057) levels remain unaltered. It was also found that group having a dose of 35 mg/kg/day; TDS showed decrease in T3 (P value 0.001), FT4 (P=0.001), TSH (P=0.003) and TRH (P=0.001) level as compared to control group. Conclusions: Our data suggest that Carbamazepine monotherapy does alter thyroid hormones and its central regulatory hormone TRH. Decrease in TRH level increase level of depression and suicidal thoughts and also risk of tertiary hypothyroidism. These findings could have very important clinical implications.